The Effect of Celery Leaf Juice (Apium graveolens Linn.) on Surface Hardness of Hot Polymerized Acrylic Resin Denture Base - Sri Wahyuningsih Rais; Bebbi Arisya Kesumaputri; Veronika Virginia S; Ainun Alya (Indonesian Dental Association, 2025)
Background: Hot polymerized acrylic resin is the most commonly used denture base material. Surface hardness is an important mechanical property of acrylic resin to resist abrasion of the denture base during routine cleaning procedures. Celery leaf juice at 50% concentration is effective as a denture cleaner. The ideal denture cleaning solution has bactericidal and fungicidal properties, is easy to use, and does not damage the materials used in making the denture. Objective: This study aims to determine the effect of celery leaf juice (Apium graveolens Linn.) on the surface hardness of hot polymerized acrylic resin denture bases. Methods: This study was a laboratory experimental study with a pre-test and post-test with control group research design. A total of 24 hot polymerized acrylic resin samples measuring 65mm x 10mm x 2.5mm were divided into 4 groups, namely 50% concentration celery leaf juice, 75% concentration celery leaf juice, alkaline peroxide, and distilled water which were immersed for 5 days. Surface hardness was measured with Vicker's Hardness Tester. Statistical tests were performed with paired T-test, One Way ANOVA parametric test and Post hoc LSD test. Results: The paired T-test showed that 3 groups, namely celery leaf juice 50% concentration, celery leaf juice 75% concentration, and alkaline peroxide had a significant decrease in surface hardness (p<0.05). Conclusion: There is an effect of celery leaf juice (Apium graveolens Linn.) on the surface hardness of hot polymerized acrylic resin denture bases. However, the hardness value is still within the tolerance limit according to ANSI/ADA specification No. 12. Keywords: hardness, celery leaf juice, hot polymerization acrylic resin